The effects of sodium hypochlorite and chlorhexidine irrigants on the antibacterial activities of alkaline media against Enterococcus faecalis. Issue 7 (July 2015) - Ma, Jinglei; Tong, Zhongchun; Ling, Junqi; Liu, Hongyan; Wei, Xi
Highlights E. faecalis survival decreased in CHX or 5.25% NaOCl and next alkaline challenge. E. faecalis biofilm survival rates were reduced in CHX and next alkaline challenge. E. faecalis biofilm survival increased in NaOCl and next alkaline challenge. CHX might be more effective in improving the alkaline than NaOCl.